Tunable Synthesis of 1, 2, 3‐Triazoles and Enamines through Deacylative Azide‐Alkene Cycloaddition. Issue 16 (21st April 2022) - Rengasamy, R.; Raj, J. Paul; Vijayalakshmi, K.; Punitha, N.; Kesavan, M.; Vajjiravel, M.; Elangovan, Jebamalai
Abstract: A tunable synthesis of 1, 4, 5‐trisubstituted 1, 2, 3‐triazoles and enamines through [3+2] cycloaddition of activated olefins and organic azides is reported. Triazoles were achieved from benzylidene diketones and organic azides by copper oxide nanoparticle catalysis while enamines were synthesized from benzylidene malonates and organic azides under solvent‐free and catalyst‐free condition. Abstract : A [3+2] cycloaddition of activated olefins and organic azides leading to 1, 4, 5‐trisubstituted 1, 2, 3‐triazoles and enamines is reported. Triazoles were achieved in good yields from benzylidene diketones and organic azides by using copper oxide nanoparticles as catalyst while enamines were synthesized in good to excellent yields from benzylidene malonates and organic azides under solvent‐free and catalyst‐free conditions.